2016
DOI: 10.1523/eneuro.0318-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Enhancement without Transient Map Expansion for Species-Specific Vocalizations in Core Auditory Cortex during Learning

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 66 publications
0
39
0
Order By: Relevance
“…Plastic changes in the maternal brain include (but are not limited to) increased reliability of neuronal responses to USVs 10 , 11 , 13 , 32 , 44 . Despite these changes, many other physiological parameters remain stable like the tonotopic representation of the cortical sheet and single unit responses to pure tones 12 , 45 . Our blind recordings and recordings from non-TRAPed cells across groups and conditions (which presumably represent a random sample of cortical neurons) provide further support to the general notion of cortical stability with respect to pure tones in mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Plastic changes in the maternal brain include (but are not limited to) increased reliability of neuronal responses to USVs 10 , 11 , 13 , 32 , 44 . Despite these changes, many other physiological parameters remain stable like the tonotopic representation of the cortical sheet and single unit responses to pure tones 12 , 45 . Our blind recordings and recordings from non-TRAPed cells across groups and conditions (which presumably represent a random sample of cortical neurons) provide further support to the general notion of cortical stability with respect to pure tones in mothers.…”
Section: Discussionmentioning
confidence: 99%
“…1B ) is observed in weaned dams (Liu and Schreiner, 2007), although a recent study reported that single-cell responses to pup calls in dams disappear at 10 days post-weaning (Tasaka et al, 2018). In the auditory cortex of lactating, as well as weaned (up to three weeks) dams, an increase in the neuronal responses to pup calls in ultrasound-responding regions, while a decrease in responses in areas which respond to low frequency sounds is observed (Shepard et al, 2016). This is paralleled by a decrease in the spontaneous activity of single neurons in weaned dams (Galindo-Leon et al, 2009; Lin et al,2013).…”
Section: Plasticity In the Auditory Cortex During Motherhoodmentioning
confidence: 99%
“…Among other changes, long-lasting plasticity in somatosensory (Rosselet et al, 2006; Xerri et al, 1994) and auditory (Cohen et al, 2011; Cohen and Mizrahi, 2015; Liu et al, 2006; Liu and Schreiner, 2007; Marlin et al, 2015; Shepard et al, 2016; Tasaka et al, 2018) cortex have recently been shown to contribute to increased responsiveness to infant cues. Most of these studies have been performed in rodents, amenable to techniques for selective monitoring and manipulation of single cells and networks in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Recent optical imaging studies have indicated that the auditory cortex of the mouse brain is composed of at least four tonotopic subfields (Issa et al, 2014) that were tentatively annotated as the dorsomedial field (DM), anterior auditory field (AAF), primary auditory cortex (A1), and secondary auditory field (A2) in a previous report (Tsukano et al, 2017). Subregions in the mouse auditory cortex may be functionally specialized (Honma et al, 2013;Baba et al, 2016;Shepard et al, 2016), and so connective patterns with other brain regions may vary according to subregion. To date, several neuronal tracing investigations have examined the afferents and efferents to/from the mouse auditory cortex.…”
Section: Introductionmentioning
confidence: 97%